To the problem of humanization of educational space of modern ukrainian school. - Kravets Volodymyr; Kikinezhdi Oksana; Shulha Iryna (Borys Grinchenko Kyiv Metropolitan University, 2018)
The article deals with the actualityof the problem of humanization of the educational space in the modern Ukrainian school through the forming a gender-equitable environment in the educational institution. The foreign experience, which concern to the research problem (concepts «gender equitable learning environment», «gender-balanced education», «gender equality in education», «gender-equitable education», «gender-fair education», «non-sexist education», «іnclusive education») is analysed. The peculiarities of forming a gender-equitable environment in an educational institution, which is based on personality oriented, competence and gender approaches are revealed.Activity of gender-equitable environment ensures the formation of gender culture and egalitarian outlook of children and youth (gender competence, sensitivity, tolerance) as important factors of personal and professional self-actualization of sexes, democratic outlook and the civic life-realization of girls and boys in the realm of national existence. The content of the gender approach and peculiarities of its introduction into the educational institution are uncovered. Our own interpretation of the concept «gender-equitable environment» as non-discriminatory, health-preservation, creative and developmental is formulated. It is based on the principles of social justice, gender equality, child-centred, egalitarianism and parity of the sexes; in which the full development of the personality is ensured, taking into account a gender, age, disability, race, culture, religion, ethnicity, etc. The structure of gender-equitable environment incluseds three components (subject-space, psychodidactic, social). The formation of a gender- equitable environment is based on the principles of «partnership pedagogy» and a gender «matrix» of humanistic pedagogical heritage, the integration of competence, personal oriented and gender approaches. The psychological and pedagogical mechanisms of formation of a gender-equitable environment for children and youth are substantiated.